1993
DOI: 10.1177/002076409303900202
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Repetition of Parasuicide: With Special Reference to Unemployment

Abstract: Economically active male parasuicides admitted to the Regional Poisoning Treatment Centre, Edinburgh in 1984 were divided into two groups--those with a previous history of parasuicide and those without. The two groups were compared on a number of psychosocial and clinical characteristics to examine which were related to repetition. A further analysis (of economically active male admissions in 1985 and 1986) tested the predictive value of these discriminating characteristics. By stratification of the population… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

1998
1998
2014
2014

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 11 publications
2
12
0
Order By: Relevance
“…This is consistent with another Australian study [14]. Other studies have noted that RPP patients tended to be older than SPP patients [15,19]. It is possible that there are geographical and cultural differences between studies.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is consistent with another Australian study [14]. Other studies have noted that RPP patients tended to be older than SPP patients [15,19]. It is possible that there are geographical and cultural differences between studies.…”
Section: Discussionsupporting
confidence: 91%
“…Similar to our study, previous studies have also found that RPP patients were more likely to be unemployed [13,18,19], single [14], live alone [20], or have a psychiatric history [13,18,19]; particularly personality disorder or schizophrenia [19] than SPP patients.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Thirteen studies, twelve of which were high-/medium-quality, reported a statistically significant association, with univariate odds ratios ranging from 1.7 (95% CI: 1.4–2.0) [24] to 4.88 (95% CI: 1.27–18.72) [25] and exceptionally high odds ratio in one study of economically active men aged 16–64 years (OR = 7.25, 95% CI: 5.22–10.05) [26]. In contrast, two high-/medium-quality studies and two low-quality studies found no statistically significant association.…”
Section: Resultsmentioning
confidence: 99%
“…To date, most studies addressing the prediction of suicide re-attempts have used no measures of predictive accuracy (Bille-Brahe et al, 1997;Cedereke and Ojehagen, 2005;Colman et al, 2004;Morton, 1993;Sidley et al, 1999), limiting the clinical utility of their findings (Galfalvy et al, 2008). However, when the precision of the prediction is measured, the results are disappointing, finding roughly 39% sensitivity and 86% specificity in a study of socio-demographic risk factors of parasuicide (Kreitman and Foster, 1991), 28% sensitivity and 99% specificity in a sample of children after deliberate self-harm (Chitsabesan et al, 2003), or 85e94% sensitivity and 26e38% specificity when assessing self-harm in emergency settings (Cooper et al, 2007).…”
Section: Introductionmentioning
confidence: 99%